2008
DOI: 10.1029/2007jb005042
|View full text |Cite
|
Sign up to set email alerts
|

Detection and localization of hydromechanical disturbances in a sandbox using the self‐potential method

Abstract: [1] Four sandbox experiments were performed to understand the self-potential response to hydro-mechanical disturbances in a water-infiltrated controlled sandbox. In the first two experiments, $0.5 mL of water was abruptly injected through a small capillary at a depth of 15 cm using a syringe impacted by a hammer stroke. In the second series of experiments, $0.5 mL of pore water was quickly pumped out of the tank, at the same depth, using a syringe. In both type of experiments, the resulting self-potential sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 78 publications
4
41
0
Order By: Relevance
“…A vigorous flow of groundwater can generate self‐potential anomalies of the order of several hundreds of millivolts [e.g., Sasai et al , 1997; Ishido et al , 1997; Lénat et al , 1998; Lewicki et al , 2003; Aizawa et al , 2005; Finizola et al , 2006] and sometimes of several volts [ Finizola et al , 2004]. Therefore, a number of researches have been conducted to model the self‐potential anomalies in terms of groundwater flow and thermohydromechanical disturbances [ Corwin and Hoover , 1979; Revil and Pezard , 1998; Revil et al , 2004, 2005; Wilkinson et al , 2005; Jardani et al , 2006; Crespy et al , 2008; Revil et al , 2008]. …”
Section: Introductionmentioning
confidence: 99%
“…A vigorous flow of groundwater can generate self‐potential anomalies of the order of several hundreds of millivolts [e.g., Sasai et al , 1997; Ishido et al , 1997; Lénat et al , 1998; Lewicki et al , 2003; Aizawa et al , 2005; Finizola et al , 2006] and sometimes of several volts [ Finizola et al , 2004]. Therefore, a number of researches have been conducted to model the self‐potential anomalies in terms of groundwater flow and thermohydromechanical disturbances [ Corwin and Hoover , 1979; Revil and Pezard , 1998; Revil et al , 2004, 2005; Wilkinson et al , 2005; Jardani et al , 2006; Crespy et al , 2008; Revil et al , 2008]. …”
Section: Introductionmentioning
confidence: 99%
“…This source arises because there is a discontinuity in the streaming potential coupling coefficient through this interface (e.g. Crespy et al . 2008 who examined a similar problem).…”
mentioning
confidence: 99%
“…The volumetric charge densityQ V is the effective charge density occurring in the pore space of the porous material because of the electrical double layer at the mineral/water interface (Leroy et al 2007(Leroy et al , 2008Jougnot et al 2009). The relationship between this volumetric charge density and the more classical streaming potential coupling coefficient C (in V Pa −1 ) has been investigated by Revil et al (2005), Linde et al (2007), Bolève et al (2007) and Crespy et al (2008). They found that C = −Q V k/σ where k and σ have been defined above.…”
Section: Field Equationsmentioning
confidence: 95%